Uji Validitas Dan Reliabilitas Kuesioner Pengukuran Kompetensi Sistem Informasi Keperawatan - Stephanie Dwi Guna; Yureya Nita (STIKes Payung Negeri Pekanbaru, 2019)
The integration of Information Technology (IT) in healthcare delivery improves the quality of care by enhancing patient safety and efficiency. Electronic health record (EHR) is one of the innovation of IT in healthcare service. EHR is commonly used in developed countries but not in developing country such as Indonesia. Prior to the implementation of a new information system, it is necessary to make sure that user can use it properly in order to achieve the maximum outcome. Nurse is the main user of the EHR in a hospital. A tool to measure the nursing informatics literacy is needed to assess nurses’ ability. One of the tool is NICAT (Nursing Informatics Competency Assessment Tool). The questionnaire was transleted into Indonesian language and was tested through validity and reliability test. The sample of this research was 233 nurses in a Public Hospital in Pekanbaru, Indonesia.The 30 items of questionnaire was valid with Cronbach’s Alpha 0.975. It can be concluded that NICAT Indonesian version is valid and reliable and can be used to assess Indonesian nurses’ nursing informatics competency.